Fish preparation. - Unknown:::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Photograph shows a group of evacuee fish butchers preparing fish for evacuees' meals at the Santa Anita, California Assembly Center.